Systemic Lupus Erythematosus and Endothelial Dysfunction: A Close Relationship - Sciatti, Edoardo; Cavazzana, Ilaria; Vizzardi, Enrico; Bonadei, Ivano; Fredi, Micaela; Taraborelli, Mara; Ferizi, Romina; Metra, Marco; Tincani, Angela; Franceschini, Franco (Current Rheumatology Reviews, 2019)
Background: Accelerated atherosclerosis, responsible for premature cardiovascular disease, has been estimated to develop or progress in 10% of systemic lupus erythematosus (SLE) patients each year and to be 6-fold more frequent in SLE compared with the general population. The mechanisms underlying accelerated atherosclerosis in SLE are complex and involve classical and “non-classical” cardiovascular risk factors. Subclinical and disseminated atherosclerosis is associated with endothelial dysfunction and arterial stiffness. Objective: The aim of this review is to analyze the association between SLE and endothelial dysfunction. Results and Conclusion: Different mechanisms have been proposed to explain the prevalence of endothelial dysfunction in SLE, which are briefly reported in this review: impaired clearance of apoptotic cells, oxidative stress markers, B cell activation with different circulating autoantibodies, different subtypes of T lymphocytes, cytokine cascade. Several studies and meta-analyses show a significant trend towards a prevalence of subclinical accelerated atherosclerosis in patients with SLE compared with healthy controls, since childhood. Based on general considerations, we suggest a multidisciplinary management to assess endothelial dysfunction at the diagnosis of the disease and to periodically search for and treat the traditional cardiovascular risk factors. Prospective studies are needed to confirm the benefits of this management.
Keywords: T lymphocytes